DIFFERENTIAL OF A GRADED QUASI-FILIFORM LEIBNIS ALGEBRA BY THE NATURAL METHOD - Murtozakulov Z. M. (Web of Journals Publishing, 2023)
The nonradical quasi-formulations of a Leibniz algebra are maxima of Leibniz algebras. The article describes Leibniz differential algebras, which are quasi-forms of the first and second types. The nilradials of the first and second types are quasi-forms of the maximum in the Leibniz algebra.
Keywords: Leibnis algebra, solvable, nilpotent, gradient, differential, nilradical.